COMMUNITY SERVICE FOR THE RESTORATION OF THE CUSTOMS ACADEMY BUILDING IN KAMPUNG TANJUNG SURAT, JOHOR, MALAYSIA - Ridho Harahap, Rasyid; Pamungkas, Okvian Dwi; Sembiring, Michael Fernando; Sugiono, Dimas; Munir, Musbakhul; Aini, Nurul; Pujianto, Danang; Harahap, Dahrul Aman; Wibowo, Edwin Agung; Hasan, Hanapi; Muhammadon, Muhammad Fairullah Bin; Siregar, Hanafi (RADJA PUBLIKA, 2025)
Kampung Tanjung Surat on Tanjung Surat Island, Kota Tinggi, Johor, is a coastal island community that has developed through ecotourism initiatives and mangrove conservation, with primary access via waterways and support from various CSR programs and university and public agency service-learning initiatives. This community service program focuses on light restoration and repainting of a support building used for community activities and field training related to the Royal Malaysian Customs Academy (AKMAL), with emphasis on coastal environmental resilience (high humidity, salt spray) and cost efficiency through community gotong royong (collective work). The measured work area is 400 m², covering the main room’s exterior–interior walls and veranda, with the selection of a weather-resistant exterior paint system, anti-alkali primer, anticorrosive coatings for metal elements, and a color scheme harmonious with local maritime culture. Work was carried out on weekends to minimize disruption to daily economic activities, resulting in improved comfort, aesthetics, and service life of the facility that supports community activities and field-learning collaboration in Tanjung Surat.